PENGARUH MODEL PEMBELAJARAN OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 5 BANGUNTAPAN - Fandi Chriswantoro Putro (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This study aims to identify trends descriptive learning outcomes Science of class VII Banguntapan 5 Junior High School academic year 2015/2016 are learning to use the Outdoor Learning models and Expository models. Comparatively aims to know is there any difference in learning outcomes Science of class VII Banguntapan 5 Junior High School academic year 2015/2016 between the learning model and the Outdoor Learning and expository models. This type of research is a Quasi-Experiment. Descriptive research results showed that the tendency of science learning achievement of class VII Banguntapan 5 Junior High School academic year 2015/2016 were learning to use the model included in the category of Outdoor Learning is very high and learning using expository models included in the high category. Comparatively, there are significant differences Science learning outcomes of students of class VII Banguntapan 5 Junior High School academic year 2015/2016 between learning using Outdoor Learning models and expository models. Means no influence learning Outdoor Learning models the learning outcomes of students of class VII Science.